AN efficient algorithm for the bottleneck product rate variation problem with precedence constraints - Dhamala, TN (Kathmandu University Journal of Science Engineering and Technology, 2011)
We consider the problem of obtaining an optimal mixed-model sequence under the just-in-time environment. Industrial applications include the production planning, real-time scheduling, response time variability and networking. The single-level problems are already solved, but they are strongly NP-hard in the multi-levels. Here, we study a bottleneck product rate variation problem with a general objective where a given set of sequences serves as chain constraints. We extend the previous result of a similar problem with min-max deviation objective in single- level. We present a pseudo-polynomial algorithm that obtains an optimal solution for the considered objective. The results are valid for precedence constraints.